Étude des interactions entre infection à ostreid herpesvirus 1, immunité, autophagie et pesticides chez l’Huître creuse, Crassostrea gigas - Moreau, Pierrick (Université de La Rochelle, Ecole doctorale Gay Lussac, 2014)
The thesis work is part of the very current issue on mass mortality outbreaks affecting Pacific oyster, C. gigas, spat and juveniles and questions about the involvement of pesticides in this phenomenon. The first part of this thesis was devoted to study the effects of pesticides on hemocyte parameters in the Pacific oyster (in vitro and in vivo). The immunomodulator effect of selected pesticides (alone or in mixture) has been explored principally through flow cytometry. The second part concerned the study of the effects of a pesticides mixture on OsHV-1 itself. No direct effects have been reported on the viral particles in presence of the pollutants. Moreover, pesticide effects on Pacific oysters were also explored through experimental pathology assays after treatment of animals with a polluant mixture. Results showed that pesticide treated oysters appeared more susceptible to the viral infection in experimental conditions. The third part concerned the study of autophagy in the Pacific oyster, C. gigas. The publication of the complete genome in 2012 has opened up new possibilities for the study of innate immunity in this species. The study of autophagy for the first time in oysters consisted in a first step in the in silico search for genes involved in this pathway and the corresponding proteins by Western blotting. Then, the role of this important process in innate immunity has been explored through reproduction infections tests with or without modulators of autophagy. Results showed that autophagy appeared as involved in defence mechanisms against viral and bacterial infection in Pacific oysters. Le travail de thèse s’inscrit dans la problématique très actuelle des mortalités massives de naissain et de juvéniles d’huîtres creuses, C. gigas, et des questionnements autour de l’implication des pesticides dans ce phénomène. La première partie de la thèse a été consacrée à l’étude des effets de pesticides sur les capacités hémocytaires de l’huître creuse (in vitro et in vivo). L’effet immunomodulateur des ...